Beneficial Impacts of MSIB Internship Program on PT Bank Mandiri (Persero) Tbk for Students in Preparing Professional Skills - Mardalena Mardalena; Sarinah Sarinah; Mukhlis Yunus; Hayati Hayati; Angra Melina (LP2M STIT Palapa Nusantara, 2024)
Internships are widely recognized as a vital component of higher education, providing students with practical experience and enhancing their employability. This research reviews existing literature to examine the impact of internships on the development of professional skills. This study employs a quantitative research method. The data in this study consists of responses regarding professional skills, social skills, and internship placements obtained through a questionnaire on Google Forms. The respondents in this study totaled 49 individuals who are participants of MSIB internship program in PT Bank Mandiri (Persero) Tbk, which come from universities all over Indonesia, including the University of Indonesia, Gadjah Mada University, Airlangga University, Malang State University, Brawijaya University, and Bandung Institute of Technology. The data obtained was then analyzed descriptively with the help of the SPSS application. At the MSIB internship program in PT Bank Mandiri (Persero) Tbk 96.74% of students stated that they gained advantages regarding professional skill while attending the internships program, while 96.16% of students were satisfied with the learning process during the internship. The findings indicate that internships significantly improve various competencies essential for career success, including effective communication, teamwork, time management, problem-solving, leadership, adaptability, stress tolerance, and decision-making. Internships also offer valuable insights into specific industries, clarify career goals, and provide opportunities for networking. Despite the overwhelmingly positive impact, areas such as leadership development and career relevance require further attention. The study suggests integrating structured internship programs into academic curricula, enhancing leadership opportunities, aligning placements with career aspirations, and providing training on soft skills. By implementing these recommendations, educational institutions and organizations can maximize the benefits of internships, ensuring that students are well-prepared for their professional careers.